What If She Earns More? Gender Norms, Income Inequality, and the Division of Housework - Iga Magda; Ewa Cukrowska-Torzewska; Marta Palczyńska (Institute of Labor Economics (IZA), 2023)
Using data from "Generation and Gender Survey" for Poland, we study the relationship between women's relative income within the household, as measured by the female share of total household income, and women's involvement in housework. We find that households in which the woman contributes more to the total household income are more likely to share housework equally. We also find that individual gender norms matter both for women's involvement in unpaid work at home and for the observed link between the female share of income and inequality between the partners in the division of housework. Women from less traditional households are found to be more likely to share housework equally. However, this negative relationship between the female share of household income and female involvement in housework is not observed among more traditional couples.
Keywords: D10; D13; D31; J12; J16; J22; 330; household income; income inequality; housework; gender norms